ASPEK BIOLOGI UBUR-UBUR API, Physalia physalis (LINNAEUS, 1758) - Mochamad Ramdhan Firdaus (Pusat Penelitian Oseanografi LIPI, 2020)
Physalia physalis is one of the jellyfish believed to be responsible for a significant proportion of jellyfish attack cases in the world. As one of the most dangerous members of the Cnidarian in the sea, P. physalis has a sting that can paralyze their prey. To humans, the sting can cause cardiotoxic, neurotoxic, musculartoxic, and hemolytic effects. P. physalis has different biological characteristics than most organisms. For example, an individual of P. physalis actually is a colony consisting of four groups of individuals who have different structures and functions. The arrangement of the colony has a complex structure and shows a polymorphism. P. physalis is a pleustonic organism because they live on the surface of the water. P. physalis still leaves many mysteries to scientists. For example, the life cycle of a P. physalis is not yet fully known. Besides, the diversity of P. physalis also still leaves questions among scientists. Some believe that P. physalis is monotypic, while others suspect there is cryptic diversity. Therefore, the study of P. physalis is very interesting, especially under the issue of climate change. Many scientists believe that jellyfish get benefit from increasing sea temperatures, so the population is predicted to increase. The high population of P. physalis threatens the sustainability of fish stocks in the ocean, mainly due to P. physalis are productive predators of fish larvae. This paper aims to provide information on the biological aspects of P. physalis, which are still limited in Indonesia.